Discussion of “Viscoelastic-plastic model of Asphalt-Roller interaction” by Fares Beainy, Sesh Commuri, Musharaf Zaman, and Imran Syed - Micaelo, R. (2014)
This paper presented an attempt to model an asphalt-roller interaction using Burger’s model, namely, the roller dynamic behavior and asphalt layer compaction evolution. Although the work of the authors is valuable and desired for better asphalt compaction understanding and the development/improvement of current intelligent compaction systems, there are some inconsistencies in the adopted methodology and a lack of information in the published paper.